2005
DOI: 10.1139/z05-133
|View full text |Cite
|
Sign up to set email alerts
|

Common vole (Microtus arvalis) population sex ratio: biases and process variation

Abstract: Vole population sex ratio varies seasonally. However, population sex ratios have usually been estimated using naïve estimators that do not allow for biases owing to the sex difference in capture probabilities and movement distances (i.e., effective areas sampled). Here we aimed to advance the methodological approach, recognizing that there are two different classes of contributing mechanisms to the pattern which are best addressed separately: (1) those mechan isms imposing a systematic error (bias) in populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…2), supposedly as a result of high resource availability in the form of tree seed production in our study region as explained in Tersago et al (2009). Prolonged breeding activity might also explain the lower sex ratio's as a similar effect was observed in common voles (Bryja et al 2005). In contrast, PUUV IgG prevalence significantly decreased in autumn 2005, even though infection was still present in eight study sites and bank vole numbers were still relatively abundant (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…2), supposedly as a result of high resource availability in the form of tree seed production in our study region as explained in Tersago et al (2009). Prolonged breeding activity might also explain the lower sex ratio's as a similar effect was observed in common voles (Bryja et al 2005). In contrast, PUUV IgG prevalence significantly decreased in autumn 2005, even though infection was still present in eight study sites and bank vole numbers were still relatively abundant (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…We initially suspected females would be more abundant than males in the general populations of both taxa as a result of agricultural tillage destroying nests, cover, and burrow systems (e.g., Witmer et al, 2007) and surviving females adjusting their reproduction to favor females in order for the population to increase (or at least remain static). Previous research showed that microtines tend to produce more females than males when population density is low (Lambin, 1994;Bond et al, 2003;Bryja et al, 2005). After tillage was reduced by converting some land to soil bank, and population density increased, we suspected the sex ratio would become more even.…”
Section: Introductionmentioning
confidence: 75%
“…Observations on reproduction in the wild of several vole species indicate greater numbers of females born in the spring and early summer and greater numbers of males born in the late summer and autumn. Researchers suggest this pattern results because it allows females to breed prior to the coming winter and males to breed the following spring (e.g., Jannett, 1981;Lambin, 1994;Bond et al, 2003;Bryja et al, 2005). Whether the females .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival, reproduction, emigration, and immigration influence the dynamics and structure of populations (Bryja et al 2005;Clutton-Brock and Coulson 2003;Krebs 2003). For instance, sexually differential survival, recruitment, and dispersal alter the sex ratio of populations.…”
Section: Discussionmentioning
confidence: 99%